Analisis Kedalaman Materi Metabolisme Sel pada Mata Pelajaran Biologi SMA Kurikulum Nasional 2013 - Aurel Cheren Nathaulia Sulistiyo; Maulida Azzra Permatasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The curriculum is a set of plans and Settings on purpose, content, and study materials and ways used as a guide to the learning activities arrangements to achieve specific goals. The lesson materials intended in the curriculum need a means to get to the learners. These are possible in various forms, one of which is in the form of a textbook. A good textbook covers all KD and conforms to established content standards. The worthiness of the text book's contents can be judged by the material completeness, the breadth of the material, and the depth of the material contained within it. This observation is intended to analyze the depth of the cell's metabolic materials on the biological subjects of the 2013 national curriculum of the high school, based on a basic competence of the 2013 curriculum from the breadth and depth of matter. The observation method used is the study of literature by searching for information on the matter of observation to be discussed. Based on analysis of some literature studies, it was obtained that the depth of discussion of metabolic materials in common biological subjects in high schools is quite deep. However, the depth varies from one school to another.